Intergenerational mobility in socio-economic status in Ethiopia - Haile, Getinet (Wiley, 2018)
Using data from two comprehensive national Labour Force Surveys and monetary and non-monetary outcomes, we examine the extent of intergenerational mobility in Ethiopia. Results from OLS and Quantile regression suggest moderate to high levels of earnings persistence. Generalised Ordered Logit based results suggest significant mobility educationally, which may be linked to the significant widening of educational opportunities over the last two decades; but hardly any evidence of mobility occupationally. Sons are found to be relatively more mobile than daughters in all cases. Public policy may have to foster the equality of opportunities generally and along gender lines to enhance mobility.